Analisis Pengaruh Uang Elektronik, Jumlah Uang Beredar, Nilai Tukar, dan Suku Bunga terhadap Inflasi di Indonesia Periode 2013-2024 - Halim, Abdul; Arituan, Bismart; Subianto, Pratiwi (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2025)
Inflation is an important economic issue and the main focus of a country's monetary policy. Nowadays, technological advances have increased the use of electronic money (e-money) as a means of payment, which has the potential to affect inflation. In addition, money supply, exchange rates, and interest rates are also factors that affect the inflation rate. This study aims to analyze the effect of e-money, money supply, exchange rates, and interest rates on inflation in Indonesia in the period 2014-2024. It used a quantitative method with a multiple linear regression approach. The data used were secondary data obtained from Bank Indonesia, Statistics Indonesia, and the Indonesian Ministry of Trade. Tests were conducted using the SPSS-25 application with various classical assumption tests such as normality, multicollinearity, heteroscedasticity, and autocorrelation. Additionally, descriptive statistical tests and partial (t-test) and simultaneous (F-test) significance tests were also applied. The results show that, partially, e-money and exchange rates had no significant effect on inflation. In contrast, money supply had a positive and significant effect on inflation, while interest rates had a significant effect with a positive direction. Simultaneously, the four independent variables significantly influence inflation with a coefficient of determination (R²) of 80.4%, which means that most of the variation in inflation can be explained by these variables. These results indicate that effective monetary policy in controlling money supply and interest rates is very important in managing inflation in Indonesia.